2012
DOI: 10.1021/nl301327d
|View full text |Cite
|
Sign up to set email alerts
|

Design Principle of Telluride-Based Nanowire Heterostructures for Potential Thermoelectric Applications

Abstract: We present a design principle to develop new categories of telluride-based thermoelectric nanowire heterostructures through rational solution-phase reactions. The catalyst-free synthesis yields Te−Bi 2 Te 3 "barbell" nanowire heterostructures with a narrow diameter and length distribution as well as a rough control over the density of the hexagonal Bi 2 Te 3 plates on the Te nanowire bodies, which can be further converted to other telluride-based compositionalmodulated nanowire heterostructures such as PbTe−Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
112
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 36 publications
(57 reference statements)
5
112
0
2
Order By: Relevance
“…[ 27 ] The work function of the TeNWs is assumed to be the same as that of bulk Te. [ 28 ] The work functions of PEDOT:PSS and rGO were measured using ultraviolet photoelectron spectroscopy (UPS), Figure S11). [ 24,29 ] The equilibrium band diagram for the ternary GDTe hybrid indicated that the energy barriers of 0.24 and 0.31 eV at the PEDOT:PSS/ TeNW and rGO/PEDOT:PSS interfaces, respectively, fi lter out low-energy carriers while they allow high-energy carriers to cross over the interface, thus enhancing the TE performance.…”
Section: Carrier Transport Characteristics Of Gdte Papermentioning
confidence: 99%
“…[ 27 ] The work function of the TeNWs is assumed to be the same as that of bulk Te. [ 28 ] The work functions of PEDOT:PSS and rGO were measured using ultraviolet photoelectron spectroscopy (UPS), Figure S11). [ 24,29 ] The equilibrium band diagram for the ternary GDTe hybrid indicated that the energy barriers of 0.24 and 0.31 eV at the PEDOT:PSS/ TeNW and rGO/PEDOT:PSS interfaces, respectively, fi lter out low-energy carriers while they allow high-energy carriers to cross over the interface, thus enhancing the TE performance.…”
Section: Carrier Transport Characteristics Of Gdte Papermentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Te/Se alloys are composed of composite Te-Se atom-bonded helical chains, which are randomly united via van der Waals forces to form highly anisotropic crystal structures. [1][2][3][4][5][6][7][8][9][10] Te/Se alloys are composed of composite Te-Se atom-bonded helical chains, which are randomly united via van der Waals forces to form highly anisotropic crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The advances include the growth of branched and hyperbranched nanowire structures [21,22], two-nanowireheterostructures-based nanocomposites [23,24], ZnO nanotetrapod bridging networks, [25] and planar nanowire cross-junction architectures. [26] These works have shown the advantages of two-dimensional cross-junction over "bridge" junction.…”
mentioning
confidence: 99%